CULTIVATING COMIDA: Dignity and Devastation in Vermont’s Dairy Industry - Mares, Teresa (Journal of Agriculture, Food Systems, and Community Development, 2018)
First paragraph: After years of challenging economic conditions, the first several months of 2018 spelled disaster for a number of Vermont’s dairy farms. As reported in a local weekly newspaper article, “Selling the Herd: A Milk Price Crisis Is Devastating Vermont’s Dairy Farms” (Heintz, 2018), the ongoing downturn in milk prices has led a number of farms to close shop. This leaves just 749 dairy farms in a state where more than 11,000 existed seven decades prior. Alongside increased costs of production, this article also reveals that dairy farmers are receiving little more for their milk than they did in the late 1970s, despite the ever-increasing costs of production and environmental pressures. The economic downturn has had a pronounced effect on smaller family farms, particularly those with fewer than 200 cows, and has affected organic and conventional dairies alike. These economic realities have exacerbated the consolidation of the industry, leaving mega-farms as those most likely to survive. These same farms are often criticized for contributing to mounting concerns about the state’s water quality and questionable labor conditions, particularly for the immigrant farmworkers who are in large part responsible for sustaining the dairy industry....